The effect of seasonality on reproductive outcome of patients undergoing intracytoplasmic sperm injection: A descriptive cross-sectional study - Marzieh Mehrafza; Maryam Asgharnia; Azadeh Raoufi; Elmira Hosseinzadeh; Sajedeh Samadnia; Zahra Atrkar Roushan (Shahid Sadoughi University of Medical Sciences, 2020)
Background: There is conflicting evidence regarding the impact of season on the assisted reproductive technology outcome. Objective: To retrospectively compare three year outcome of women undergoing their first intracytoplasmic sperm injection cycle, across seasons. Materials and Methods: In this descriptive cross-sectional study, 3,670 women who underwent their first intracytoplasmic sperm injection cycle in Mehr Medical Institute, Rasht, Iran between April 2010 and May 2014 were studied. Women were divided into four groups according to the day of oocyte retrival as: spring (n = 808), summer (n = 994), autumn (n = 1066), and winter (n = 802). Basal and stimulation charecteristics were compared among groups. Results: While sperm concentration and motility were significantly lower during summer, the total number of retrieved and metaphase II oocytes were significantly higher (p = 0.0001, p = 0.0001, p = 0.004, p = 0.02, respectively). Fertilization rate were significantly higher during autumn (p = 0.0001). Also, the number of high- quality transferred embryos were significantly higher during summer and winter (p = 0.03). A similar pattern was observed in implantation rate and pregnancy over the four seasons Conclusion: Despite the fact that intracytoplasmic sperm injection minimize the seasonal effect on pregnancy outcome, changes in pregnancy rate still occur among different seasons without particular pattern. It seems that performing assisted reproductive technology procedures in a particular season should be considered as an effective factor.